Gibberellic acid decreases Melanocallis caryaefoliae (Hemiptera: Aphididae) population density and chlorotic feeding injury to foliage in pecan orchards. Issue 3 (22nd November 2020) - Cottrell, Ted E; Wood, Bruce W
Abstract: BACKGROUND: Melanocallis caryaefoliae (Davis), Monellia caryella (Fitch), and Monelliopsis pecanis Bissell (Hemiptera: Aphididae) attack pecan foliage ( Carya illinoinensis [Wangenh.] K. Koch). Unlike M. caryella and M. pecanis, feeding by M. caryaefoliae triggers a physiological change within foliage mimicking natural leaf senescence; it can lead to defoliation. Pretreatment of pecan foliage with gibberellic acid (GA3 ) mitigates M. caryaefoliae ‐elicited physiological disturbances. GA3 application to pecan was evaluated for efficacy regarding effects on M. caryaefoliae populations and possible negative side‐effects on two natural enemy species and on return bloom of pecan. RESULTS: All GA3 treatment rate schedules significantly reduced M. caryaefoliae nymphs but not adults or adults and nymphs of M. caryella or M. pecanis . Percentage leaf chlorosis elicited by M. caryaefoliae was significantly reduced by GA3 ( i.e., 39.5 to 197.7 g a.i./ha). No negative side‐effects of GA3 treatment were detected regarding certain key natural enemy species or on return bloom of pecan. CONCULUSION: Application of GA3 to the orchard canopy protects foliage from senescence‐like physiological responses triggered by M. caryaefoliae . This reduces detrimental leaflet chlorosis, both senescence and abscission processes and horticulturally significant feeding injury. Additionally, the absence of apparent negative side‐effects on key natural enemies and return bloom is suggestive of a practical means for efficacious non‐insecticidal control of M. caryaefoliae populations in orchards. This novel protective effect of GA3 against aphid‐elicited, senescence‐like physiological responses may merit investigation as an IPM tool to manage aphid species eliciting similar senescence‐like damage to other crop species. Published 2020. This article is a U.S. Government work and is in the public domain in the USA. Abstract : The black pecan aphid elicits chlorotic feeding zones on pecan foliage for feeding. Pretreatment of foliage with gibberellic acid mitigates elicitation of chlorosis and negatively impacts the aphid's population density.